1947
DOI: 10.1038/bjc.1947.15
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the Breast. An Analysis of the Symptoms, Factors Affecting Prognosis, Results of Treatment and Recurrences in 1211 Cases Treated at the Middlesex Hospital

Abstract: Tins investigation was undertaken to bring up to date the records of the Middlesex Hospital, and to attempt to discover whether there was any statistical evidence to support commonly held views on factors affecting prognosis and methods of treatment. 836 cases of carcinoma of the female breast treated during the years 1926-35 were analysed and a smaller group of 265 cases, treated during the years 1936-40, were the subject of a further investigation to discover the effect of more modern methods of treatment.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The mortality figure of the present series is of the same order as that of Truscott (1947) who, in an analysis of 1101 cases of carcinoma of the breast operated on at the Middlesex Hospital between 1926 and 1940 inclusive, found that 72% of traced cases had died of the disease. The results in the present series can therefore probably be regarded as typical of those obtaining with the methods of selection and treatment then practiced.…”
Section: Discussionsupporting
confidence: 70%
“…The mortality figure of the present series is of the same order as that of Truscott (1947) who, in an analysis of 1101 cases of carcinoma of the breast operated on at the Middlesex Hospital between 1926 and 1940 inclusive, found that 72% of traced cases had died of the disease. The results in the present series can therefore probably be regarded as typical of those obtaining with the methods of selection and treatment then practiced.…”
Section: Discussionsupporting
confidence: 70%
“…[1][2][3][4][5][6][7] In present series, Most of the patients of carcinoma breast presented in stage II 32 (45.7%) followed by 23 (32.8%) in stage III, 12 (17.1%) patients presented with stage IV diseases while only three (4.2%) patients in stage I disease. According to Samina et al, The striking difference in the stage distribution of breast cancer patients in the developing and developed countries has been largely attributed to the lack of screening facilities, delays in seeking medical attention, poor socioeconomic status, poor health care systems and poor diagnostic and therapeutic facilities in developing countries.…”
Section: Shrivastava N Et Al Int Surg J 2016 Aug;3(3):1156-1162mentioning
confidence: 91%
“…BRCA1 is a tumour suppressor gene located on chromosome 17 (17q21) and accounts for 40% of familial breast cancer. BRCA2 is located on chromosome 13(13q12-13) and accounts for about 30% of familial breast cancer [4].…”
Section: Introductionmentioning
confidence: 99%